Young Children Selectively Imitate Models Conforming to Social Norms - Oláh, Katalin; Király, Ildikó (Frontiers in Psychology, 2019)
This study investigated whether toddlers would selectively imitate a demonstrator who exhibits familiarity with cultural practices in their tool-using habits over a demonstrator who consistently uses tools in an unconventional way. 3-year-old children (n=45) watched videos depicting two models, one of whom performed tool-using actions in a conventional way, while the other model deviated from social conventions. Then, both models introduced a technique to build a tower (differing in one element). Moreover, the context of the demonstration was also manipulated: in one condition, the models expressed their teaching intentions, while in the other, they performed the actions without communicative signals. Children were more willing to copy the actions of the conventionally behaving model, irrespective of the context of the demonstration.